When Does ICT-Enabled Citizen Voice Lead to Government Responsiveness? - Peixoto, Tiago; Fox, Jonathan (World Bank, Washington, DC, 2016)
This paper reviews evidence on the use of 23 information and communication technology (ICT) platforms to project citizen voice to improve public service delivery. This meta-analysis focuses on empirical studies of initiatives in the global South, highlighting both citizen uptake (‘yelp’) and the degree to which public service providers respond to expressions of citizen voice (‘teeth’). The conceptual framework further distinguishes between two trajectories for ICT-enabled citizen voice: Upwards accountability occurs when users provide feedback directly to decision-makers in real time, allowing policy-makers and program managers to identify and address service delivery problems – but at their discretion. Downwards accountability, in contrast, occurs either through real time user feedback or less immediate forms of collective civic action that publicly call on service providers to become more accountable and depends less exclusively on decision- makers’ discretion about whether or not to act on the information provided. This distinction between the ways in which ICT platforms mediate the relationship between citizens and service providers allows for a precise analytical focus on how different dimensions of such platforms contribute to public sector responsiveness. These cases suggest that while ICT platforms have been relevant in increasing policymakers’ and senior managers’ capacity to respond, most of them have yet to influence their willingness to do so.